Cost-benefit analysis method for building solutions - Araújo, Catarina (2016)
The building sector is responsible for consuming approximately 40% of the final energy in Europe. However, more than 50% of this consumption can be reduced through energy-efficient measures. Our society is facing not only a severe and unprecedented environmental crisis but also an economic crisis of similar magnitude. In light of this, EU has developed legislation promoting the use of the Cost-Optimal (CO) method in order to improve building energy efficiency, in which selection criteria is based on life cycle costs. Nevertheless, studies show that the implementation of energy-efficient solutions is far from ideal. Therefore, it is very important to analyse the reasons for this gap between theory and implementation as well as improve selection methods. This study aims to develop a methodology based on a cost-effectiveness analysis, which can be seen as an improvement to the CO method as it considers the investment willingness of stakeholders in the selection process of energy-efficient solutions. The method uses a simple graphical display in which the stakeholdersâ investment willingness is identified as the slope of a reference line, allowing easy selection between building solutions. This method will lead to the selection of more desired â from stakeholdersâ point of view â and more energy-efficient solutions than those selected through the CO method.